Method of Takhshîsh with Al-‘urf and Its Presence in Madura’s Traditional Rule - Fahruddin Ali Sabri (Karsa: Journal of Social and Islamic Culture, 2016)
Basically, there is no contradiction of the quranic instruction and the sunnah (prophet tradition). The contradictive perspective is only exist in the mind of the mujtahid. Among the kinds of spesification (takhshih) is specification through custom (al urf). If the spesification through custom which is elaborated by ulema of ushuul al fiqh (the foundation of  Islamic jurisprudence) correlated with the Madurese customary law, it will be assumed that this contradicts with the Madurese customary law. This descriptive library research proves tha some part of Madurese custom can specify the general diction or lafd such as in the case of endowement of money for mosque and sale the living corp. But some of Madurese custom lawa can not specify the general diction or lafd such as in the custom of salep tarjha and the marriage of the second daughter.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i1.1011